Edukasi Pemberian Vitamin A sebagai Upaya Preventif Stunting pada Balita di Posyandu Nanas Karangroto - Sulistyianingsih, Sulistyianingsih; Falakhudin, Anim; Azkiya, Annisa; Ananda, Bintang; Margarete, Caroline; Labibah, Hasna; Nadhifah, Milatun (Kolaborasi Masyarakat, 2025)
Stunting remains a major nutritional problem affecting children’s growth and development in Indonesia. Vitamin A deficiency is one of the contributing factors, as this micronutrient plays a vital role in maintaining immune function, supporting growth, and protecting against infection-related growth impairment. Community education is essential to increase parental awareness of the importance of vitamin A in preventing stunting. This qualitative descriptive study was conducted at Nanas Posyandu, Karangroto Village, Semarang City, on February 12, 2025, involving 25 parents and their 25 toddlers. The educational activity lasted 60 minutes and included counseling sessions using posters, leaflets, and vitamin A capsule models. The session covered the functions of vitamin A, recommended supplementation schedules, and signs of deficiency that may increase the risk of stunting. Data were collected through field observations, participant feedback, and documentation, then analyzed qualitatively to describe participants’ engagement and understanding. The results showed increased awareness and improved understanding among parents regarding the broader role of vitamin A, not only for vision but also for immune support and growth. Participants actively engaged in discussions and demonstrated positive responses to the community-based education. This activity highlights that participatory health education at the community level can enhance nutrition literacy and support the sustainability of national stunting prevention programs. It is recommended that similar educational initiatives be implemented regularly, involving Posyandu cadres and local health workers to reach more families with young children.